Ultrasound features of some abdominal and genital organs of apparently healthy Palawan bearcats (Arctictis binturong whitei, J.A. ALLEN, 1910) (MAMMALIA CARNIVORA: VIVERRIDAE) - Lajara, Eoin Q.; Sales, Shirley Faye D.; Lastica-Ternura, Emilia A.; Acorda, Jezie (2021)
The study determined the ultrasound features of some abdominal and genital organs of seven apparently healthy Palawan bearcats (Arctictis binturong whitei, J.A. Allen, 1909) using an ultrasound machine equipped with a multifrequency microconvex scanner. The liver and gallbladder were visualized at the level of the xiphisternum region caudal from the diaphragm. The liver showed hypoechoic parenchyma with distinct hyperechoic capsule while the gallbladder showed hyperechoic wall and anechoic lumen with grainy periphery. The spleen was scanned at the left lateral side of the abdomen and showed homogeneous hypoechoic parenchyma with a distinct hyperechoic capsule. The left and right kidneys were scanned from the left and right flanks of the pelvic area and appeared as rounded, bean-shaped organs with an anechoic to hypoechoic medulla, a hyperechoic sinus and cortex, and a hyperechoic capsule. The oval-shaped urinary bladder appeared as an anechoic lumen enclosed by a hyperechoic wall and was visualized at the pelvic area. In males, the prostate gland located caudal to the urinary bladder exhibited echogenic prostatic parenchyma covered by a hyperechoic capsule. The oval-shaped testes featured a mildly echogenic tunica albuginea and hypoechoic parenchyma. The ultrasound features obtained in this study could be used as reference in assessing disorders and diseases of some abdominal organs of the Palawan bearcat.
Keywords: Veterinary ultrasonography; Genitalia; Urogenital system